2016
DOI: 10.21037/jgo.2016.11.06
|View full text |Cite
|
Sign up to set email alerts
|

Successful hepatectomy for metastatic squamous cell carcinoma of the anal canal—a case report

Abstract: Abstract:Despite rare, metastatic anal carcinoma confers a poor prognosis. Systemic chemotherapy is the mainstay of treatment for advanced disease while the role of biologics and/or surgical resection of metastatic disease are anecdotal. Compared to isolated liver colorectal or neuroendocrine cancer liver metastases, there is far less experience with resection or nonsurgical local ablative procedures for patients with metastatic anal carcinoma to the liver. We report the case of a 67-year-old woman with metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Specifically, squamous cell carcinoma accounts for 75% of anal cancer cases in the United States and Europe [ 4 , 8 ]. Despite its rarity, the incidence of anal cancer has been increasing over the past three decades [ 9 ] likely due to changing trends in sexual behavior, smoking, HPV or HIV infection, and immune suppression in transplant recipients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, squamous cell carcinoma accounts for 75% of anal cancer cases in the United States and Europe [ 4 , 8 ]. Despite its rarity, the incidence of anal cancer has been increasing over the past three decades [ 9 ] likely due to changing trends in sexual behavior, smoking, HPV or HIV infection, and immune suppression in transplant recipients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although no studies have reported evidence of the efficacy of resection of distant metastasis alone, some have reported improved prognosis from radiation in combination with resection of distant metastasis [ 9 ]. Pawlick et al reported on 27 patients in a multicenter analysis of hepatic resection for anal canal squamous cell carcinoma metastasized to the liver.…”
Section: Discussionmentioning
confidence: 99%